Implementation of Multi-Tiered Systems of Support (MTSS) In Education: Challenges, Strategies, And Impact On Students' Social-Emotional Development: A Scoping Review - Choirunissa, Risza; Nugraheni, Sri Achadi; Purnami, Cahya Tri; Wahyuningsih, Nur Endah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
The Multi-Tiered Systems of Support (MTSS) framework is pivotal in educational settings, designed to enhance student outcomes through structured support systems that address academic, behavioral, and social-emotional needs. This scoping review explores the complexities of implementing MTSS, identifies effective strategies, and assesses its impact on students' social-emotional development. The review analyzed articles source from Google Scholar, PubMed, and ScienceDirect as a database with a range of publications between 2019-2023 using the keywords: Adolescents, Multi-Tiered Systems of Support, Education and adolescents. There were 18 articles that met the inclusion criteria. The findings suggest that when effectively implemented, MTSS significantly improves social-emotional development. This involves strategic planning, interdisciplinary collaboration, culturally responsive practices, and active participation of families and communities. School leadership plays a vital role in coordinating these efforts, while culturally relevant practices and teacher self-assessment tools help address the diverse needs of students. Additionally, family involvement is a crucial factor in enhancing academic performance and reducing behavioral issues, contributing to the overall social-emotional development of students. A well-coordinated strategy is necessary to optimize the effectiveness of MTSS and improve student outcomes.